A study on awareness of Malaysian muslims toward wasiyyah practice / Ili 'Aifaa Mohd Johar and Maryam Jameelah Jumadin - Mohd Johar, Ili 'Aifaa; Jumadin, Maryam Jameelah (Faculty of Business and Management, 2013)
This study aim to investigate the awareness of Malaysian Muslims towards wasiyyah practice. The objective of this study are to investigate the level of awareness of Malaysian Muslims toward wasiyyah practice, to indentify the relationship between Independent Variable (knowledge and cultural value) and Dependent Variable (awareness of wasiyyah practice) and to indentify the most important factor that influence the awareness of wasiyyah practice. The finding found that the level of awareness of Malaysian Muslims toward wasiyyah practice is moderate. The correlation between knowledge and awareness of wasiyyah practice is weak while the correlation between cultural values and awareness of wasiyyah practice is good. So, the conclusion is the most influence factor that effect the level of awareness of Malaysian Muslims towards wasiyyah practice is cultural value.